PENGATURAN TINDAK PIDANA ILLEGAL CONTENT PERSPEKTIF RESTORATIVE JUSTICE DI MASA YANG AKAN DATANG (IUS CONSTITUENDUM) - I Made Wahyu Chandra Satriana; Ni Made Liana Dewi; I Putu Anton Maha Dippayana (Jurnal Komunikasi Hukum, 2023)
The settlement of illegal content crimes in Law Number 19 of 2016 concerning Electronic Information and Transactions, which has a paradigm of retaliation using criminal law, has caused many reactions for justice seekers. Thus it is necessary to conduct research on the regulation of illegal content criminal acts from the perspective of restorative justice as a legal profile in the future. The issues raised in this study are regulation of illegal content criminal acts from a restorative justice perspective in the future (ius constituendum) and policies for solving illegal content crimes from a restorative justice perspective in the future (ius constituendum). The absence of legal norms in this study is the absence of restorative justice arrangements in the settlement of illegal content crimes in Law number 19 of 2016 concerning Information and Electronic Transactions. The results of this study are that the regulation of illegal content criminal acts from a restorative justice perspective in the future (ius constituendum) refers to the Regulation of the Indonesian National Police Number 8 of 2021 concerning Handling of Crimes Based on Restorative Justice which in principle prioritizes peaceful processes and avoids retaliation in the form of criminal. The policy at the investigation stage for the settlement of illegal content criminal acts from the perspective of restorative justice in the future (ius constituendum) is carried out by stopping the investigation at the investigative level for the sake of law.